PERAN FINANCIAL SOSIALIZATION, FINANCIAL SELF-EFFICACY DAN FINANCIAL KNOWLEDGE TERHADAP FINANCIAL MANAGEMENT BEHAVIOR GENERASI Z - Firdaus, Alifia Firmanda; Kadarningsih, Ana (Pusat Riset dan Inovasi Nasional, 2023)
Generation Z is an age group ranging from 17 to 25 years. Generation Z has the principle of You Only Live Once (YOLO) where this principle refers to consumer behavior. To minimize consumptive behavior, good financial management habits are needed. Of course, there are several factors that can influence financial management behavior itself. The aim of this research is to test and analyze whether financial socialization, financial self-efficacy, and financial knowledge have a positive and significant effect on the financial management behavior of Generation Z students. The population in this research are active students at Dian Nuswantoro University, Faculty of Economics and Business, class 2020 to 2022. The sampling technique involves distributing questionnaires online via Google Forms. SEM-PLS was chosen to obtain results using the smartPLS version 3.2.8 tool. The main finding in this research is that the financial socialization and financial knowledge variables have a positive and significant influence on the financial management behavior of generation Z students. Meanwhile, the financial self-efficacy variable does not have a significant influence on the financial management behavior of generation Z students.